Selection for drought resistance in common bean also improves yield in phosphorus limited and favorable environments - Beebe, Stephen E.; Rao, Idupulapati M.; Cajiao V., César Hernando; Grajales Bedoya, Miguel Angel (Wiley, 2008)
An estimated 60% of common bean (Phaseolus vulgaris L.) production worldwide is at risk of drought. A breeding program was developed at the International Center of Tropical Agriculture (CIAT) to create drought resistant breeding lines with varietal potential in the small red, small black, cream (mulatinho) and cream-striped (carioca) grain classes. Breeding populations were created from triple or double crosses. Field screening under terminal drought was performed at Palmira, Colombia in the dry season in F2, F3:5, and F6:8 generations over two cycles of recurrent selection in the small red and small black classes, and one cycle in the mulatinho and carioca classes. Drought resistant lines yielded significantly more than commercial check cultivars under drought in all color classes. Some outyielded the respective checks by 15 to 25% (depending on color class and trial) in one or more of three favorable environments, or in the combined analysis across favorable environments, and were also earlier to mature. Drought resistant lines presented up to 36% greater yield d?1 in favorable environments. Some also expressed superior yields in a phosphorus-limited environment. Thus, selection for drought resistance has improved yield potential and plant efficiency across different environments. It is suggested that selection under drought stress reveals genes that correct inefficiencies inherited from the wild Phaseolus vulgaris, and are key to yield improvement of common bean.